2013
DOI: 10.1111/jeb.12192
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to a novel male during late pregnancy influences subsequent growth of offspring during lactation

Abstract: In mammals, allocation to reproduction can either be primed or suppressed in relation to cues from other individuals. Some conspecifics (e.g. potential mates) may enhance an individual's ability to reproduce but others may have a detrimental effect on reproductive success. One widely studied response to conspecific cues, the 'Bruce effect', occurs when pregnant females abort their pregnancies after exposure to a novel male. It has been suggested that this response has evolved as a counter-tactic to the threat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…Our results support the prediction that the “late Bruce effect,” in which female mice exposed to a novel male late in pregnancy weaned at lower weights (Gale et al., ), may be due to a strategic reduction in maternal investment in lactation. It is notable that females exposed to a novel male's scent spent less time nursing pups than females exposed to the scent of their mate.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results support the prediction that the “late Bruce effect,” in which female mice exposed to a novel male late in pregnancy weaned at lower weights (Gale et al., ), may be due to a strategic reduction in maternal investment in lactation. It is notable that females exposed to a novel male's scent spent less time nursing pups than females exposed to the scent of their mate.…”
Section: Discussionsupporting
confidence: 89%
“…As in our previous study (Gale et al., ), the offspring of the females that were exposed to the novel male were smaller at the end of lactation, but they caught up in size by maturity. The catch‐up growth exhibited by the offspring coincides with the time after lactation when offspring begin to feed themselves on solid food.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In these species, the blastocyst is prevented from successful implantation after exposure to a nonsire male without the need for male aggression (see below). After successful implantation, however, laboratory experiments in these species have shown that exposure to a novel male no longer induces pregnancy failure, although it can cause a reduction in investment by females (e.g., smaller pups at birth) . All documented instances of male‐mediated implantation failure are more consistent with the Bruce effect than with feticide.…”
Section: When Can Male‐mediated Prenatal Loss Occur?mentioning
confidence: 97%
“…Mice are a useful organism to study transgenerational effects because development can be modified by both maternal (Mateo & Maestripieri, ) and paternal (Rando, ) inputs. Maternal and paternal effects are often detected as a modulation of offspring growth rate during and after gestation (Gale, Gibson, Brooks, & Garratt, ; Grandjean et al, ; Mashoodh, Franks, Curley, & Champagne, ; McPherson, Owens, Fullston, & Lane, ). Converging evidence suggests that these parental effects are mediated in part by reprogramming of metabolic transcription, particularly in the liver (Rando & Simmons, ).…”
Section: Introductionmentioning
confidence: 99%